Carbon nanotube@manganese oxide nanosheet core-shell structure encapsulated within reduced graphene oxide film for flexible all-solid-state asymmetric supercapacitors. (June 2018) - Wu, Shuxing; Hui, Kwan San; Hui, Kwun Nam
Abstract: To achieve flexible energy storage devices with high performance, a new class of flexible electrodes with exquisite architectures that provide well-defined pathways for efficient ionic and electronic transport is highly needed. A flexible 3D electrode is fabricated based on assembling 1D carbon nanotube@manganese oxide (MnO2 ) nanosheet core-shell structures (CM) with 2D reduced graphene oxide (rGO) nanosheets. MnO2 nanosheets are grafted vertically along the carbon nanotube backbone through a secondary (seeded) growth. Flexible hybrid films (GCM) composed of CM and rGO are prepared by vacuum filtration of the mixed dispersions of both components assisted by electrostatic interactions. By adopting this ternary hybrid architecture, the GCM electrode exhibits exceptional charge storage capability in 1 M Na2 SO4 aqueous electrolyte with high specific capacitance (298 F g −1 at 0.5 A g −1 ), good rate capability, and high cycling stability (90.3% retention over 5000 cycles). A highly flexible all-solid-state asymmetrical supercapacitor is assembled with GCM as the positive electrode and holey graphene film spaced with carbon sphere (H-GCS) as the negative electrode. GCM//H-GCS asymmetric supercapacitor delivers a maximum energy density of 24.6 Wh kg −1 and a power density of 9005.3 W kg −1 with excellent cycle life of 75.9% retention after 10 000 cycles. Graphical abstract: Image 1